The effect of phenotypic switching on the biological properties of candida krusei / Mohd Hafiz Arzmi - Mohd Hafiz, Arzmi (2011)
Candida krusei has been identified as an emerging pathogen after Candida albicans and Candida glabrata. Until today, the ability to switch its phenotype in unfavourable environment has not been reported in Candida krusei. This study was carried out in order to evaluate the phenotypic switching ability of Candida krusei and to access how this ability affects the biological properties, adherence capacity and susceptibility towards chlorhexidine (CHX), amphotericin B, nystatin, Piper betle and Nigella sativa aqueous extracts. To induce the switched generations, Candida krusei was cultured on yeast extract potato dextrose (YEPD) agar containing 0.05% of phloxine B. Following a 5-day incubation, the colony forming units (CFU/mL) were examined and determined. This phenotypically switched colony was designated as the 1st cell generation. The cells from the 1st generation were subcultured following the same protocol to produce the 2nd, 3rd and 4th generation of switched cells. The 1st and 2nd switched generations were observed to exhibit similar colony morphology comparative to the unswitched Candida krusei. The percentages of recovery population for the 1st and 2nd generations were reduced to 46.6% and 36.4%, respectively. The colonies from the 3rd and 4th switched generations were found to be highly myceliated with the former exhibiting lobate margin and the later with filamentous margin. Interestingly, the percentage of recovery for the 3rd generation showed a tremendous increased to 85.7% but was reduced to 70.8% in the 4th generation. SEM micrographs revealed the surface appearance of the unswitched Candida krusei, 1st and 2nd generations as smooth, with the 2nd generation having more extended pseudohyphae compared to the other generations. In contrast, the surface of the 3rd and the 4th generations were with rough surfaces. The 4th generation also exhibited pimpled or punctate morphology with short pseudohyphae. The unswitched Candida krusei and the 3rd switched generations were also observed to have deposits of iii extracellular matrix on its surfaces. The adherence capacity of Candida krusei also showed variations in all cell generations. The 2nd switched generation showed the highest adherence with total population of (154.0 ± 60.2) x 102 CFU/mL to the saliva-coated glass beads while the unswitched Candida krusei showed the least adherence at (5.65 ± 0.5) x 102 CFU/mL. Based on the disc diffusion test, the degree of susceptibility towards CHX, amphotericin B, nystatin and Piper betle were found to differ in all generations of Candida krusei. The unswitched Candida krusei was found to be the most susceptible towards CHX and the 2nd generation was the least susceptible. The 3rd unswitched Candida krusei was found to be the most susceptible towards amphotericin B and the unswitched generation was the least susceptible. The 4th generation was determined as the most susceptible towards nystatin in contrast to the 2nd generation which showed the least. In the susceptibility study towards Piper betle results indicated that the 1st generation was the most susceptible while the 4th generation was the least. The MIC and MFC of Candida krusei for the unswitched and all switched generations towards CHX, amphotericin B, nystatin and Piper betle were determined at 0.4 μg/μL, 50 μg/mL, 10 unit/mL and 12.5 mg/mL respectively. From the growth curve study, the unswitched and all switched generations of Candida krusei showed varying degree of responses towards CHX, amphotericin B and Piper betle treated environment. These results suggested that Candida krusei is able to switching ability is a virulence factor of Candida krusei which affects the biological properties, adherence ability and susceptibility towards CHX, amphotericin B, nystatin and Piper betle. Thus, it leads to the pathogenic property in the oral cavity.